Effects of war crimes in the Rome Statute on the system of national prosecutions. With particular emphasis on universal jurisdiction - Varga, Réka (The ICC at 25: Lessons Learnt, 2025)
This chapter explores the interplay between the International Criminal Court (ICC) and domestic legal systems, focusing on how war crimes provisions influence national prosecution efforts. Emphasizing the ICC's principle of complementarity, the analysis highlights both the legal obligations and the practical challenges faced by national courts in prosecuting core international crimes. It demonstrates the critical importance of adequate domestic legislation and judicial capacity, particularly in systems where the direct application of international law remains limited or ambiguous. The study addresses difficulties in implementing treaty and customary international law, revealing gaps in national legal frameworks and judicial preparedness. A special focus is given to the re-emergence of universal jurisdiction, particularly in light of the Russian-Ukrainian conflict. The chapter discusses Ukraine’s partial incorporation in its legislation of the Rome Statute's definitions and the efforts of European and overseas states in initiating war crimes investigations based on universal or extraterritorial jurisdiction. These developments illustrate both the promise and the complexity of international criminal justice when national systems are tasked with upholding global norms. The chapter concludes by reaffirming the vital role of national courts in closing the impunity gap and stresses that the ICC’s success depends largely on states fulfilling their responsibility to prosecute war crimes effectively, guided by international legal standards and supported through coordinated global efforts. Keywords: International Criminal Justice, War Crimes Prosecution, Domestic Courts, Russian-Ukrainian Conflict, Universal Jurisdiction